Morphometric Studies of Accessions of Duranta erecta L. (Vebernaceae) Complex in Nigeria : Morphometric studies of Duranta erecta in Nigeria - ABDULQUADRI SAGAYA; ABDULLAHI ALANAMU ABDULRAHAMAN (Borneo Journal of Resource Science and Technology, 2023)
Studies were conducted to broaden the systematic knowledge of the genus Duranta erecta L., to contribute a better understanding of their taxonomic and evolutionary relationships. Previous studies have pointed out complexity in the taxonomy and nomenclature of the species. A total of 224 samples were collected from six geo-political zones of Nigeria, and were grouped into 38 accessions. The plants were compared using 21 morphological characters involving qualitative and quantitative characteristics. Multivariate analyses such as Principal Component Analysis (PCA) and Cluster Analysis (CA) were employed to evaluate the intraspecific variabilities. The results showed that all the plants exhibited significant differences in all the quantitative attributes with the variegated type having the longest and widest leaves ranging from 12.20 cm and 5.08 cm, respectively. The qualitative characters delimited the plants accessions into distinctive groups of eight morphological forms namely; green bush, yellow bush, variegated yellow, variegated white, variegated yellow double, plain yellow, broad green, thorny green type. The PCA showed that leaf length, leaf width, internode length and length of inflorescence were some of the quantitative characters while leaf shape, leaf colour, leaf margin, flower colour and leaf apex are some of the qualitative traits that accounted for the delimitation. Unpaired Weighted Group Multivariate Analysis (UPGMA) using the Euclidian separated the 38 accessions into two major clusters; cluster I (flower producing) and cluster II (non-flower producing) Duranta erecta. Morphological variations and field observations suggested that there could be gene flow among the accessions of Duranta erecta studied and gene flow is an important factor in population genetics, shaping the diversity of species.